The use of digitalis in family medicine - Santos, Rita Manuela Lopes Dos (2001)
Objectives: To assess adequacy of therapy with digoxin and its monitoring in primary health care. Type of Study: Descriptive, cross-sectional Setting: Sete Rios Health Centre Benfica Outpost Population: Patients whose electronic clinical record had notes for prescription of digoxin. Methodology: Data were collected from clinical records using a form which consisted of closed questions on demographic data and patients clinical status. Results: Sixty-three patients were on digoxin, 88.9% of which were elderly. Their mean age was 74.4 years, with a Standard Deviation of 10.2 years. In this study, 25 (36.9%) patients met adequacy criteria, 7 (11.1%) had no indication for digitalics, and for the remaining 31 (49.2%) the unavailability of ancillary diagnostic exams characterising their atrial fibrillation and heart failure made it impossible to assess therapeutic adequacy. Six patients presented associated conditions. Half of the patients were simultaneously taking drugs which interfere with digoxins pharmacokinetics, and three quarters were on diuretics. Of the 63 patients, only eight had records of their serum digoxin levels, and for only two was there a shorter than 10 months gap. Conclusion: The results show that in around half of the patients adequacy of digoxin use cannot be assessed, and that serum concentrations of digoxin were not much valued. This may be explained by recording deficiencies, or by the fact that starting and monitoring digitalis therapy is delegated on to a cardiologist.